Evaluation of changes in retinal and choroidal thickness using spectral domain optical coherence tomography in unilateral non granulomatous acute anterior uveitis - Balcı, Özlem; Tanrıverdi, Cafer; Aydın, Ali; Özsütçü, Mustafa; Gülkılık, Gökhan; Kocabora, Mehmet Selim (Elsevier Masson SAS, 2019)
Purpose: To assess retinal and choroidal thickness changes in eyes with a first episode of unilateral non granulomatous acute anterior uveitis (AU). Methods: Thirty-one patients with acute unilateral non granulomatous AU who had undergone spectral domain optical coherence tomography (SD-OCT) of both eyes were included in this retrospective study. Retinal thickness (RT) as defined by the Early Treatment Diabetic Retinopathy Study (ETDRS) and subfoveal choroidal thickness (SFCT) obtained by SD-OCT were recorded. Healthy fellow eyes of the patients served as the control. Results: A significant thickening in 1 mm of ETDRS subfield and in subfoveal choroid was observed in eyes with acute AU when compared with the unaffected fellow eyes (P = 0.005 and P < 0.00001, respectively). RT and SFCT of affected eyes did not show a significant difference in terms of HLA-B27 antigen presence or absence (P > 0.05, for all). Conclusions: Significant posterior segment changes were detected in eyes with acute unilateral non granulomatous

Objectif. — Évaluer les changements d’épaisseur rétinienne et choroïdienne dans les yeux lorsdu premier épisode d’uvéite antérieure aiguë unilatérale non granulomateuse (UA).Patients et méthodes. — Trente et un patients atteints d’UA aiguë unilatérale non granuloma-teuse qui avaient bénéficié d’une tomographie par cohérence optique en domaine spectral(SD-OCT) des deux yeux ont été inclus dans cette étude rétrospective. L’épaisseur rétinienne(ER) définie par le groupe ETDRS (Early Treatment Diabetic Retinopathy Study) et l’épaisseurde la choroïde sous-fovéale (ECSF) obtenue par SD-OCT ont été évaluées. Les yeux sains despatients ont été acceptés comme yeux témoins.Résultats. — Un épaississement significatif dans 1 mm de sous-champ ETDRS et dans la choroïdesous-fovéolaire a été observé dans les yeux atteints d’UA aiguë par rapport aux yeux témoins(p = 0,005 et p < 0,00001, respectivement). Les ER et ECSF des yeux affectés n’ont pas montré dedifférence significative en termes de présence ou d’absence de l’antigène HLA-B27 (p > 0,05).Conclusions. — Des modifications significatives du segment postérieur ont été détectées dansles yeux atteints d’UA aiguë unilatérale non granulomateuse.
Évaluation des changements de l’épaisseur rétinienne et choroïdienne par tomographie par cohérence optique en domaine spectral dans l'uvéite antérieure aiguë unilatéral non granulomateuse
Keywords: Anterior Uveitis; Optical Coherence Tomography; Retinal Thickness; Subfoveal Choroidal Thickness; D’uvéite Antérieure; Tomographie Par Cohérence Optique; Épaisseur Rétinienne; Épaisseur Choroïdienne Sous-Fovéale